Social Systems Matter: Precision Medicine, Public Health, and the Medical Model. Issue 4 (2nd October 2021) - Sun, Shirley; Ching, Ann Hui
Abstract: Drawing on data from semi-structured interviews conducted in Singapore, Canada, and the United States, this paper shows that biomedical experts are deeply concerned about the shortcomings of the biomedical model of health. Precision public health, when anchored in genomics, can be considered a twenty-first century version of the medical model of health, which originated from nineteenth century germ theory. First, concerns regarding the adoption of genetic testing to identify disease susceptibility, and limitations of genome-based disease prevention exist. This includes limited evidence of the utility of screening measures in reducing mortality, lack of reimbursement for genetic screening, negative implications of genetic screening, and limitations of race/ethnicity-based genetic screening. Second, there are also concerns regarding the treatment of diseases, particularly the management of the costs of treatment and genetic testing in the context of national public health systems. Ultimately, it was found that healthcare-related inequities can be reduced in a universal, publicly funded, single-payer healthcare setting. These findings provide strong evidence supporting the social model of health by highlighting the key role of social systems and non-clinical interventions in precision public health to improve health outcomes for all.